2015
DOI: 10.1080/10810730.2015.1018572
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Written Administration of the Short Literacy Survey

Abstract: Most health literacy assessments are time consuming and are administered verbally. Written self-administration of measures may facilitate more widespread assessment of health literacy. The aim of this study was to determine the inter-method reliability and concurrent validity of the written administration of the three subjective health literacy questions of the Short Literacy Survey (SLS). The Rapid Estimate of Adult Literacy in Medicine (REALM) and the shortened Test of Functional Health Literacy in Adults (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Previous studies of health literacy in dialysis used these assessments. We recently reported that the three-item BHLS is valid when administered as either a verbal interview or as a written self-administration [ 37 ]. Although trained research personnel supervised administration in this study of hemodialysis patients, we have also recently reported that assessment by a clinical nurse in routine care is comparable with that of formally trained personnel [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of health literacy in dialysis used these assessments. We recently reported that the three-item BHLS is valid when administered as either a verbal interview or as a written self-administration [ 37 ]. Although trained research personnel supervised administration in this study of hemodialysis patients, we have also recently reported that assessment by a clinical nurse in routine care is comparable with that of formally trained personnel [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women self‐reported the highest grade or level of school that they had completed, annual household income from all sources, overall health status, and mammogram frequency. We measured health literacy with a scale developed by Chew et al and summed the 3 items for a continuous health literacy score (possible range, 3‐15) . We assessed numeracy with the Subjective Numeracy Scale (possible range, 1‐6) .…”
Section: Methodsmentioning
confidence: 99%
“…We measured health literacy with a scale developed by Chew et al 26 and summed the 3 items for a continuous health literacy score (possible range, [3][4][5][6][7][8][9][10][11][12][13][14][15]. 27 We assessed numeracy with the Subjective Numeracy Scale (possible range, 1-6). 28,29 Women were asked to report what they thought the chance was that they would develop breast cancer in the next 5 years (from 0% [no chance] to 100% [definitely will]).…”
Section: Patient Covariatesmentioning
confidence: 99%
“…These questions are valid for assessment of health literacy both via written and verbal administration in the transplant evaluation population (27). The questions are summed totaling 3-15 and then dichotomized into limited (total score=3-9) or adequate (total score=10-15) health literacy (28).…”
Section: Methodsmentioning
confidence: 99%